Human (Clovis)–gomphothere (Cuvieronius sp.) association ∼13,390 calibrated yBP in Sonora, Mexico - Sanchez, Guadalupe (National Academy of Sciences, 2014)
The earliest known foragers to populate most of North America south of the glaciers [∼11,500 to ≥ ∼10,800 (14)C yBP; ∼13,300 to ∼12,800 calibrated (Cal) years] made distinctive “Clovis” artifacts. They are stereotypically characterized as hunters of Pleistocene megamammals (mostly mammoth) who entered the continent via Beringia and an ice-free corridor in Canada. The origins of Clovis technology are unclear, however, with no obvious evidence of a predecessor to the north. Here we present evidence for Clovis hunting and habitation ∼11,550 yBP (∼13,390 Cal years) at “El Fin del Mundo,” an archaeological site in Sonora, northwestern Mexico. The site also includes the first evidence to our knowledge for gomphothere (Cuvieronius sp.) as Clovis prey, otherwise unknown in the North American archaeological record and terminal Pleistocene paleontological record. These data (i) broaden the age and geographic range for Clovis, establishing El Fin del Mundo as one of the oldest and southernmost in situ Clovis sites, supporting the hypothesis that Clovis had its origins well south of the gateways into the continent, and (ii) expand the make-up of the North American megafauna community just before extinction.